SOME BIOECOLOGICAL FEATURES OF THE DYER’S BROOM - (GENISTA TINCTORIA) (Scientific journal of the Fergana State University, 2024)
At present, in the climatic conditions of Fergana region, bringing the drake plant from other places and acclimatizing it here, obtaining its seeds, creating highly viable varieties and forms by crossing local growing forms, reproducing them through modern methods and creating ornamental plants. It is also very important to study all the aspects of plants from the cytoembryological point of view, such as the formation of generative and vegetative organs, developmental progress, microsporogenesis and megosporogenesis, endospermogenesis and embryogenesis, double fertilization, when used as a plant and for various other purposes. is important.